DORADD: Deterministic Parallel Execution in the Era of Microsecond-Scale Computing - Liu, Zhengqing; Unal, Musa; Parkinson, Matthew J.; Kogias, Marios (PPoPP '25, 2025)
Deterministic parallelism is a key building block for distributed and fault-tolerant systems that offers substantial performance benefits while guaranteeing determinism. By studying existing deterministically parallel systems (DPS), we identify certain design pitfalls, such as batched execution and inefficient runtime synchronization, that preclude them from meeting the demands of μs-scale and high-throughput distributed systems deployed in modern datacenters. We present DORADD, a deterministically parallel runtime with low latency and high throughput, designed for modern datacenter services. DORADD introduces a hybrid scheduling scheme that effectively decouples request dispatching from execution. It employs a single dispatcher to deterministically construct a dynamic dependency graph of incoming requests and worker pools that can independently execute requests in a work-conserving and synchronization-free manner. Furthermore, DORADD overcomes the single-dispatcher throughput bottleneck based on core pipelining. We use DORADD to build an in-memory database and compare it with Caracal, the current state-of-the-art deterministic database, via the YCSB and TPC-C benchmarks. Our evaluation shows up to 2.5× better throughput and more than 150× and 300× better tail latency in non-contended and contended cases, respectively. We also compare DORADD with Caladan, the state-of-the-art non-deterministic remote procedure call (RPC) scheduler, and demonstrate that determinism in DORADD does not incur any performance overhead.